Service Pragmatics as a Tool for State Crisis Management Examples from German, French, Austrian and Hungarian Legal History - Balázs Sallai (Journal on European History of Law)
The nation-states of 19th and 20th century Europe often created, or at least tried to create, so-called service pragmatics, that incorporated the most important issues of public service law, such as the rights and duties of officials. In many cases, the codification processes were preceded by a kind of struggle, as the civil servants involved tried to apply the code, that conflicted with the government’s interests on several points. It also happened, however, that the interests of the government dictated the codification, for example in some crisis period of state life, when such a code of laws was hoped for restabilization. This study also focuses on the latter phenomenon, in which, through some successful or unsuccessful examples, I try to shed light on how the codification of service pragmatics can be used as a tool for state crisis management.